Relationships between the menstrual cycle and neuropsychiatric and physical symptoms in females with Tourette syndrome - Daisy T. Noriega-Makarskyy; Evan Realbuto; Ariadne Kaylor; Lisa Osiecki; Angela Essa; Dongmei Yu; Dongmei Yu; Cornelia Illmann; Carol A. Mathews; Carol A. Mathews; Carol A. Mathews; Jeremiah M. Scharf; et al. (Frontiers in Neurology)
BackgroundThe effects of the menstrual cycle on neuropsychiatric and physical symptoms have been examined in multiple psychiatric illnesses, but research on Tourette syndrome (TS) and menstruation is limited and inconclusive. One study published in 1992 reported that 34% of female respondents experienced tic fluctuations with their menstrual cycles; however, a subsequent 2001 study found no significant relationship between menstrual cycle-related hormonal changes and tic symptoms across participants. There has been no further published exploration of this topic in the intervening 20+ years, and thus these discrepant results have not been reconciled. The current study aimed to assess tic changes across the menstrual cycle and to explore clinical predictors of tic fluctuations in adult females with TS.MethodsAn online survey was completed by 112 of 315 eligible female adults with TS. Respondents were asked to share their age of TS symptom onset, history of OCD and ADHD diagnoses, and current tic symptoms and severity. Participants also retrospectively reported their experiences with fluctuations in tics and other physical and psychiatric symptoms over the course of the menstrual cycle.Results26% of the 112 respondents endorsed tic changes in relation to their menstrual cycles. Univariable and multivariable logistic regression demonstrated that higher current tic severity and impairment as well as co-occurring cycle-related mood and anxiety changes significantly predicted the presence of self-reported tic fluctuations during the menstrual cycle.DiscussionResults suggest that some females with TS experience changes in tic symptoms during their menstrual cycles, although future research is required to clarify the complex relationships between the menstrual cycle, tics, and other psychiatric symptoms. The low response rate, retrospective recall of symptoms, and lack of information about hormonal influences such as contraceptives and menopause are notable study limitations.